Endoscopic Lateral Neck Dissection: A New Frontier in Endoscopic Thyroid Surgery - Zhang, Zeyu; Sun, Botao; Ouyang, Hui; Cong, Rong; Xia, Fada; Li, Xinying (Frontiers in Endocrinology, 2021)
Background: Endoscopic and robotic thyroidectomy are effective and safe surgical options for thyroid surgery, with excellent cosmetic outcomes. However, in regard to lateral neck dissection (LND), much effort is required to alleviate cervical disfigurement derived from a long incision. Technologic innovations have allowed for endoscopic LND, without the need for extended cervical incisions and providing access to remote sites, including axillary, chest-breast, face-lift, transoral, and hybrid approaches. Methods: A comprehensive review of published literature was performed using the search terms "lateral neck dissection", "thyroid", and "endoscopy OR endoscopic OR endoscope OR robotic" in PubMed. Results: This review provides an overview of the current knowledge regarding endoscopic LND and it specifically addresses the following points: (1) the surgical procedure, (2) the indications and contraindications, (3) the complications and surgical outcomes, and (4) the technical advantages and limitations. Robotic LND, totally endoscopic LND, and endoscope-assisted LND are separately discussed. Conclusions: Endoscopic LND is a feasible and safe technique in terms of complete resection of the selected neck levels, complications, and cosmetic outcomes. However, it is recommended to strictly select criteria when expanding the population of eligible patients. A formal indication for endoscopic LND has not yet been established. Thus, a well-designed, multicentre study with a large cohort is necessary to confirm the feasibility, long-term outcomes, oncological safety, and influence of endoscopic LND on patient QoL.